Enhanced Electrochemiluminescence of Porphyrin-Based Metal–Organic Frameworks Controlled via Coordination Modulation - Cai, Wen-Rong; Zeng, Hai-Bo; Xue, Huai-Guo; Marks, Robert S; Cosnier, Serge; Zhang, Xue-Ji; Shan, Dan (Analytical chemistry (Washington), 2020)
Precise control over the composition, morphology, and size of porphyrin-based metal–organic frameworks is challenging, but the extension of these hybrid materials will enable the creation of novel electrochemiluminescence (ECL) emitters. The coordination of various entities is made from Zn2+ ions and meso-tetra(4-carboxyphenyl)porphine (TCPP), modulated by both solvent and bathophenanthrolinedisulfonic acid disodium salt (BPS) as capping agent, resulting in limited crystal growth of Zn-TCPP in DMF/H2O (v/v, 1:1) and the formation of nanoscale TCPP-Zn-BPS. The role of BPS is also evaluated using Zn-TCPP and BPS-Zn-TCPP as controls, prepared in the absence of BPS and different coordinating sequences of ligands, respectively. The newly obtained TCPP-Zn-BPS exhibits a variety of different morphologies, as well as spectral and optoelectronic properties. The ECL behavior of TCPP-Zn-BPS is investigated by using H2O2 as co-reactant. The amplification of ECL is further studied by ECL spectroscopies and cyclic voltammetry, with the corresponding mechanism proposed.